UNIVERSITY STUDENTS’ PERCEPTIONS OF DIFFICULTIES ON CONVEYING THE ARGUMENT IN ONLINE DISCUSSION DURING THE PANDEMIC COVID 19 - Pratiwi, Sulistya Ningsih (Universitas Suryakancana, 2022)
During the 2019 corona pandemic, Indonesia itself decided to conduct online learning, both at schools and universities. Students are required to carry out the virtual learning process in their respective homes. One of the ways in which online classes take place is to conduct online discussions between students. Therefore in this study, the researchers conducted research with the aim of finding out what difficulties students faced in presenting their arguments in online discussions during this corona pandemic. Researchers used qualitative methods through online surveys by giving several questions to correspondents in the form of questionnaires using google form. There are 34 students who are willing to be correspondents in our research this time. The reseachers produce so many surprising facts that have been experienced by students when online discussions take place. Some students did experience difficulties in delivering arguments in online discussion sessions ranging from not being confident and also lack of knowledge in building arguments. There is a lot that needs to be evaluated about the way lecturers make this online discussion in order that students are better prepared to convey their arguments in online discussion.Â